2003
DOI: 10.1023/b:reio.0000031366.28559.c1
|View full text |Cite
|
Sign up to set email alerts
|

Common Properties and Sectoral Specificities in the Dynamics of U.S. Manufacturing Companies

Abstract: The size distribution and growth rate dynamics of U.S. companieshave been extensively studied by many authors. In this paper,using the COMPUSTAT database, we extend the analysis todisaggregated data, studying 15 sectors of the U.S.manufacturing industry. The sectoral investigation reveals thepresence of general statistical properties that can be consideredvalid across all the studied sectors. In particular, theprobability density of firms growth rates invariably displays acharacteristic tent shape and the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
108
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 13 publications
18
108
2
2
Order By: Relevance
“…We treat the introduction of new products and packs as potentially endogenous and instrument for these variables in a dynamic growth model. Similar to some of other studies (e.g., Dunne andHughes, 1994, Bottazzi andSecchi, 2003) we find that smaller firms grow faster than larger ones. Our main result is that the introduction of new formulations, as well as of new packs, has a significant impact on growth in the short run, but only new forms have a long term effect on growth.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…We treat the introduction of new products and packs as potentially endogenous and instrument for these variables in a dynamic growth model. Similar to some of other studies (e.g., Dunne andHughes, 1994, Bottazzi andSecchi, 2003) we find that smaller firms grow faster than larger ones. Our main result is that the introduction of new formulations, as well as of new packs, has a significant impact on growth in the short run, but only new forms have a long term effect on growth.…”
Section: Introductionsupporting
confidence: 80%
“…2 On the other hand, lack of such positive relationship is reported in Geroski et al (1997) and Bottazzi et al (2001).…”
Section: Introductionmentioning
confidence: 78%
“…I will explain below why statistical analyses performed from the economists' standpoint are generally untrustworthy, with few exceptions [20]. Our alternative to taking advice from economics texts and papers for the purpose of modelling markets will be stated below.…”
Section: Should Econophysicistsmentioning
confidence: 99%
“…Early studies have found no relationship between rate of growth and size of the firm (Hart, 1962;Hymer and Pashigan, 1962). But most of the later studies have found a negative relation between firm size and growth contrary to Gibrat"s law (Kumar, 1985;Hall, 1987;Dunne and Hughes, 1994;Almus and Nerlinger, 2000;Bottazzi and Secchi, 2003). Though, empirical literature on the relationship between firm size and growth has for the most part rejected the stochastic model, some have found weak evidence to support Gibrat"s law for larger firms (Mansfield, 1962;Evans, 1987).…”
Section: Determinants Of Firm Growthmentioning
confidence: 91%